Archaeobotanical analyses of kitchen waste of Jever Castle, 17th/18th century - dating - Bittmann, Felix (Niedersächsisches Institut für historische Küstenforschung, Wilhelmshaven, 2023)
During restoration works in the castle of Jever, Lower Saxony, a hidden niche in the former kitchen wall was found filled-up with wate material: botanical remains, bones, insects, molluscs, bricks, mortar. The analysis revealed a large number of plant species both local and imported (Olea). In addition, bones of mammaly, birds, fishes and amphibia were identified.
Keywords: archaeobotany; Archaeology